Метод отримання метилових ефірів для дизельних двигунів з жирів тваринного походження - Постол, Юлія Олександрівна; Postol, Yuliia; Стручаєв, М.І.; Гулевський, Вадим Борисович; Hulevskyi, Vadym (Мелітополь, ТДАТУ, 2019)
UKR: Розглянуто спосіб виробництва складних метилових ефірів із жирів тваринного походження для отримання біологічної добавки до дизельного пального. Збільшення забруднення навколишнього середовища, погіршення екологічних умов за рахунок збільшення споживання енергії з мінеральних ресурсів, а також швидкого виснаження корисних ресурсів та високих цін змушують шукати альтернативні види палива, отримані з поновлюваних джерел. Найбільш переважними видами рідкого біопалива є біодизельне паливо та біоетанол. Сучасні уявлення про правильне харчування залишають тваринам жирів все менше місця в нашому раціоні. На підприємствах м'ясної промисловості накопичуються значні обсяги жирної сировини, що не споживається основним виробництвом. Його знешкодження, як і продажі, є малоприбутковою справою, а в деяких випадках просто збитковою. Крім того, після очищення флотації стічних вод на очисних спорудах утворюються жирові відходи, що також потрібно утилізовувати. За нинішніх цін на вуглеводневу сировину тисячі тонн жирових відходів перетворюються на потенційне джерело додаткової енергії та додаткового прибутку. Запропоновано простий спосіб використання жирових відходів для отримання біопалива з максимальним розділенням сирого гліцерину та домішок. Ключові слова: метилові ефіри, дизельний двигун, кавітація. /////////////// ENG:The mean of production of difficult methyl ethers is considered from fats of animal origin for the receipt of biological addition to the diesel fuel. Increasing environmental pollution, deteriorating environmental conditions through increased consumption of energy from mineral resources, along with the rapid depletion of useful resources and high prices have led scientists to seek alternative fuels derived from renewable sources. The most preferred types of liquid biofuels are biodiesel and bioethanol. Modern ideas about proper nutrition leave animal fats less and less space in our diet. Significant volumes of fatty raw materials not consumed by the main production are accumulated at the enterprises of the meat industry. Its disposal, as well as sales, is a low-profit business, and in some cases simply unprofitable. In addition, after treatment of wastewater flotation, the wastewater treatment plants generate fatty waste, which also needs to be done. At current prices for hydrocarbon raw materials, thousands of tons of fat waste are being transformed into a potential source of additional energy and additional revenue. Easy way suggested to use animal fat waste to produce biofuels with maximum separation of crude glycerol and impurities should be implemented. The essence of the technological process is as follows. The technical animal fat is ground to a paste-like state in the cutter, then fed into the furnace boiler by means of a conveyor. The furnace boiler is heated to the required temperature. After melting and evaporating the water, the liquid animal fat enters the intermediate tank thermos, where it cools to the desired temperature. The next step is the supply of fat to the esterification reactor, where it is mixed with the required amount of catalyst with potassium hydroxide and methyl alcohol methanol. The resulting heated mixture is sent to a tank for upholding. In this case, the glycerol together with the hydroxyl cleaved from the acid molecule and the non-reacting glycerides drops down, and the bioadditive floats upwards due to differences in density.
METHOD OF RECEIPT OF METHYL ETHERS FOR DIESEL ENGINES FROM FATS OF ANIMAL ORIGIN
Keywords: methyl esters; diesel engine; cavitation; метилові ефіри; дизельний двигун; кавітація